(untitled) (The Review of Diabetic Studies, 2024)
Antimicrobial resistance (AMR) is an increasing health challenge in the world, especially among patients with severe health problems who are infected with multidrug resistant organisms (MDROs). The altered pharmacokinetics (PK) in these patients may not respond to standard antimicrobial treatment because of dysfunction of the organs, hypoalbuminemia as well as fluid shifts. This poses a major problem of maximizing the use of antimicrobial therapy to achieve adequate exposure of the drug at the point of infection. One potential mode of improving therapeutic outcomes is through clinical pharmacy interventions especially those that are supported by pharmacokinetic/pharmacodynamic (PK/PD) principles. Such interventions are individual dosing schedules and therapeutic drug monitoring (TDM), that is, it considers the physiological changes and infection dynamics of the patient. Critical is the necessity of the accurate dose, under-dose may cause the failure of treatment and the rise of additional resistance, whereas over-dose may cause toxicity. This review takes a complex look at drug resistance, host pharmacokinetic variability, and how clinical pharmacy can be useful in optimizing antimicrobial treatment. It highlights the need to use individualized dosing in enhancing treatment efficacy and minimize the occurrence of resistance. Furthermore, it contributes to the inclusion of sophisticated pharmacokinetic and TDM models into the standard of clinical practice to ensure the best therapeutic use of critical patients.